Refining the nuclear localization signal within the Egr transcriptional coregulator NAB2. Issue 1 (21st November 2018) - LaVallee, Jacquelyn; Grant, Terrain; D'Angelo‐Early, Stephanie; Kletsov, Sergey; Berry, Nicole A.; Abt, Kimberly M.; Bloch, Christopher P.; Muscedere, Mario L.; Adams, Kenneth W.
Abstract : NAB1 and 2 are coregulators for early growth response (Egr) transcription factors. The NAB1 nuclear localization signal (NLS) was previously described as a bipartite NLS of sequence R(X2 )K(X11 )KRXK. The sequence is conserved in NAB2 as K(X2 )R(X11 )KKXK; however, whether it functions as the NAB2 NLS has not been tested. We show that the KKXK motif in NAB2 is necessary and sufficient to mediate nuclear localization. Mutation of the KKXK motif to AAXA causes cytoplasmic localization of NAB2, while Lys/Arg‐to‐Ala mutations of the upstream K(X2 )R motif have no effect. Fusion of the KKXK motif to cytoplasmic protein eIF2Bε causes nuclear localization. Altogether, this study refines our knowledge of the NAB2 NLS, demonstrating that KKXK343‐346 is necessary and sufficient for nuclear localization. Abstract :